Electronically controllable grounded inductance simulators using single commercially available IC: LT1228 - Siripongdee, Surapong; Jaikla, Winai (My University, 2017)
The grounded inductance simulators using available commercially integrated circuit (IC) are proposed in this paper. The three types of active inductor called parallel R and L, series R and L and pure L are achieved. The proposed inductance simulators consist of single available commercially IC from Linear Technology Inc. called LT1228 with a resistor and a capacitor. The tune of inductance and resistance value can be done electronically. The proposed inductance simulators don't require any active and passive component matching condition. The performances of proposed circuit are verified through PSPICE simulation and experiment. To show the usability of the proposed simulators, they are used to realize the sinusoidal oscillator, second order bandpass filter and second order band-reject filter. The workability of these applications is experimented. The results agree well with theoretical expect.
Keywords: Inductance simulator; LT1228; Oscillator; Parallel R-L; Series R-L